Genetic characterization of multiple insecticide resistances in Cydia pomonella (L.) using RNAseq - Olivares, Jérôme; Barrès, Benoit; Gauffre, Bertrand; Idier, Mathilda; Siegwart, Myriam; Maugin, Sandrine (Entomologia generalis, 2023)
The codling moth, Cydia pomonella, is a major pest of apple and pear orchards. However, with intensive use of pesticide, an increasing number of resistances has been reported. Detoxification is one of the main mechanisms involved in resistance in Lepidoptera, and there is still much to discover about the molecular mechanisms underlying it. This study was conducted to decipher the molecular mechanisms involved in the insecticide resistance of C. pomonella and to identify genetic markers associated with resistance upon exposure to several pesticides. To that aim, an experimental evolution was carried out from a wild population resistant to several active substances. We generated three lines by combining genetic crosses and experimental selection using chlorantraniliprole, deltamethrin and spinosad. High throughput RNA-sequencing (RNA-seq) was performed on the three lines to verify whether similar mechanisms were involved in pesticide resistance across lines and to assess the role of detoxification and other mechanisms in resistance. In total, we found 592 mutations and 157 differentially expressed genes. Of the candidate genes identified as involved in resistance, a very limited number were shared between lines. We found in total 20 genes belonging to already known candidate genes, with 2 of them known to be involved in C. pomonella resistance (CYP4C1 and CYP6B2) and identified several genes that have never been linked with resistance before (mainly associated with odorant perception and stress).